2004
DOI: 10.1021/ie020733n
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics of Amino Acid Decomposition in High-Temperature and High-Pressure Water

Abstract: Decomposition behavior of five selected amino acids in high-temperature and high-pressure water was studied using a continuous-flow tubular reactor. The reaction was carried out in the temperature range of 200−340 °C at a pressure of 20 MPa. Alanine and its derivatives leucine, phenylalanine, serine, and aspartic acid were used as model amino acids. The effect of temperature on reaction products, pathway, and rate was determined as a function of reaction time. Alanine decomposed into lactic acid and pyruvic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
198
1
13

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(230 citation statements)
references
References 25 publications
18
198
1
13
Order By: Relevance
“…The two reactions occurred simultaneously and the competition between the two reactions exists under hydrothermal conditions. Sato et al [46] investigated the characteristics of HTL of five types of amino acids. It was reported that the ratio of decarboxylation/ deamination was affected by the type of amino acid.…”
Section: Proteinsmentioning
confidence: 99%
“…The two reactions occurred simultaneously and the competition between the two reactions exists under hydrothermal conditions. Sato et al [46] investigated the characteristics of HTL of five types of amino acids. It was reported that the ratio of decarboxylation/ deamination was affected by the type of amino acid.…”
Section: Proteinsmentioning
confidence: 99%
“…Already at 160 °C, the content of total amino acids and amines starts to increase with time very slowly, whereas at 190 °C and higher temperatures, this increase becomes quite drastic. At 240 °C, a decrease in amino acids and amine content can be noticed, which probably indicates the formation of other amino compounds, such as ammonia 4 . Because ammonia is a gas at room temperature, it was probably removed in the solvent separation step.…”
Section: Total Amino Acids and Amines Contentmentioning
confidence: 99%
“…has been found to be quite useful, especially in waste and biomass processing technologies. Nevertheless, for food processing, these degradation reactions can have a negative effect on the foods structure itself, resulting in an altered structure with lower quality or even formation of toxic compounds 3,4 . It is therefore important, that these hydrothermally induced reactions be studied in more detail in order to know how and when they occur.…”
Section: Introductionmentioning
confidence: 99%
“…A corresponding reduction in carbon monoxide yield supports this idea. Considering that amino groups can produce ammonia or amine molecules, as was observed by Sato et al 39) , the alkalinity of the liquid should also increase with feedstock concentration. This alkali might have functioned as the catalyst for the water gas shift reaction.…”
Section: Effect Of Feedstock Concentrationmentioning
confidence: 77%
“…However, Sato et al 39) have analyzed the products from alanine decomposition in high pressure and high temperature condition, and detected ammonia and ethyl amine as nitrogen containing compounds. This behavior of nitrogen will be our next target.…”
Section: Effect Of Reaction Temperaturementioning
confidence: 99%